RURAL TOURISM DEVELOPMENT IN RASINA DISTRICT - Žarevac Bošković, Milica; Lakićević, Marija; Pantović, Danijela (Economics of Agriculture, 2022)
The purpose of this paper is to present the current situation in the development of rural tourism in the Rasina district, as well as to suggest possible solutions to the recorded problems. For that purpose, empirical research was conducted in Lomnica, Kupci, Kukljin, Jasika, Gornji Stepoš, Naupare, Trmčare on a sample of 288 respondents who live in these places and are engaged in agricultural work and rural tourism. The data obtained through the survey of respondents was processed and the t-test for independent samples was applied, as well as the analysis of variance. The obtained results indicate that there are no statistically significant differences in the attitudes of respondents in relation to gender and age. Also, it was determined that the respondents are aware of the advantages and disadvantages of the area in which they live regarding the development of rural tourism. In line with this, support and cooperation of the public and private sectors are needed, to improve the existing potential.